The Acting Chair's Summing Up Independent Evaluation Office-IMF Engagement with Small Developing States : Executive Board Meeting May 6, 2022. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2022)
Executive Directors welcomed the report of the Independent Evaluation Office (IEO) on IMF Engagement with Small Developing States (SDS) and appreciated its insights and recommendations. They welcomed the report's finding that the Fund has substantially stepped up its engagement with its SDS members over the past decade, and that SDS country officials generally considered Fund surveillance and capacity development (CD) activities of high quality and well-tailored to their needs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Global Warming; Monetary Policy; Natural Disasters and Their Management; Political Economy